Efektivitas dan Risiko Penggunaan M-Banking pada Bank Syariah Indonesia Terhadap Kepuasan Pelanggan - Susanto, Is; Mukri, Moh.; Bahrudin, Moh.; Hanif, Hanif (Jurnal Manajemen Bisnis dan Keuangan, 2022)
Mobile banking is a service provided by a bank that allows customers to carry out various types of transactions anytime and anywhere through mobile media. This service is not only used by customers in general, but UIN students as current customers have also used these services in paying tuition bills. However, most students still do not take advantage of the convenience of these services. This study aims to determine the effect of the effectiveness and risk of using m-banking services at Bank Syariah Indonesia on customer satisfaction. This study uses a quantitative approach. The population of this study was all students of UIN class of 2019 totaling 6,435. The results of this study are the effectiveness variable does not partially affect customer satisfaction in the use of m-banking services at Bank Syariah Indonesia, while the risk variable has a significant positive effect on customer satisfaction in using m-banking services at Bank Syariah Indonesia.